Identification and characterization of the causative triatomine bugs of anaphylactic shock in Zhanjiang, China - Ya-Lan Huang; Da-Na Huang; Wei-Hua Wu; Fan Yang; Xiao-Min Zhang; Miao Wang; Yi-Jun Tang; Qian Zhang; Li-Fei Peng; Ren-Li Zhang (BMC, 2018)
Abstract Background Two health concerns primarily related to triatomine bugs are transmission of Trypanosoma cruzi through infective feces, and allergic reactions induced by triatomine bites. In the Southwestern United States, reduviid bugs bites commonly cause insect allergy. In South China, four cases of anaphylactic shock have been reported after this bite exposure. To further classify the species of these bugs and confirm the sensitization of the triatomine saliva, we caught triatomine bugs from the region where the bites occurred and performed phylogenetic and immunohistochemical (IHC) analysis. Methods Triatomine bugs were collected in Donghai Island of Zhanjiang City in South China. The genomic DNA was extracted from three legs of the bugs. The fragments of mitochondrial 16S rRNA, cytochrome c oxidase subunit I (COI) gene and nuclear ribosomal 18S and 28S rRNA genes were obtained by PCR and sequenced. A phylogenetic tree was constructed based on the sequence of 16S rRNA gene using a maximum likelihood method with MEGA 7.0 software. Trypanosomal specific fragments and vertebrate COI genes were amplified from the fecal DNA to detect the infection of trypanosomes and analyze the blood feeding patterns, respectively. Paraffin-embedded sections were then prepared from adult triatomines and sent for IHC staining. Results We collected two adult triatomine bugs in Donghai Island. Morphological and molecular analyses indicated that the triatomines were Triatoma rubrofasciata. No fragments of T. cruzi or other trypanosomes were detected from the fecal DNA. Mitochondrial gene segments of Homo sapiens and Mus musculus were successfully amplified. The allergens which induced specific IgE antibodies in human serum were localized in the triatomine saliva by IHC assay. Conclusions The two triatomine bugs from Donghai Island were T. rubrofasciata. They had bitten humans and mice. Their saliva should contain the allergens related to the allergic symptoms and even anaphylactic shock of exposed residents. Great consideration should be given to this triatomine bugs due to their considerable distribution and potential threat to public health in South China.